(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to analyze the current state of the nursing workforce and identify the factors affecting it at Tien Giang provincial General Hospital. Research methods: Using cross-sectional descriptive method combining quantitative (data from reports and management software) and qualitative (in-depth interviews with 10 people, group discussion). Results: The data shows that the hospital has 771 nurses, of which 46.2% have a university degree and 43.3% have a college degree. There is a shortage of staff in specialized departments such as emergency care and surgery. The recruitment of nurses has increased from 27 in 2022 to 45 in 2024, but it still does not meet the demand. Conclusions: The hospital needs to improve compensation, working conditions, and training opportunities to enhance the quality and stability of the nursing workforce, particularly in specialized departments.